The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.5194/aab-60-213-2017
|View full text |Cite
|
Sign up to set email alerts
|

Effects of gender and diet on back fat and loin area ultrasound measurements during the growth and final stage of fattening in Iberian pigs

Abstract: Abstract. Reared in extensive parcels, 50 castrated or spayed Iberian pigs were fattened with conventional or high-oleic-concentrate diets to evaluate the effect of diet and sex on the measurements of the loin area depth, back fat thickness and its layers during the last 6 months before slaughter at eight time points in two anatomical locations by serial scans. The scan was the factor that had the greatest influence, followed by sex and diet. Back fat thickness at 10th rib level was higher than at 14th rib lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 57 publications
(63 reference statements)
1
0
0
Order By: Relevance
“…In the same way, these authors reported a slight increase over the finished fattening period in the external subcutaneous layer compared to the medium and internal ones, the medium layer representing nearly 60% of the total backfat [ 39 ]. A similar trend was observed by González et al [ 40 ], who reported that the middle layer of backfat showed more growth than the inner layer, with the outer layer demonstrating the lowest fat thickness. In contrast, the increase in backfat thickness in pigs fed on low-protein diets has been previously reported [ 5 ].…”
Section: Discussionsupporting
confidence: 87%
“…In the same way, these authors reported a slight increase over the finished fattening period in the external subcutaneous layer compared to the medium and internal ones, the medium layer representing nearly 60% of the total backfat [ 39 ]. A similar trend was observed by González et al [ 40 ], who reported that the middle layer of backfat showed more growth than the inner layer, with the outer layer demonstrating the lowest fat thickness. In contrast, the increase in backfat thickness in pigs fed on low-protein diets has been previously reported [ 5 ].…”
Section: Discussionsupporting
confidence: 87%